The concise Oxford dictionary of archaeology - Darvill, Timothy (New York : Oxford University Press, 2008)
A useful ready-reference archaeological resource with more than 4000 entries arranged alphabetically and coded by type, e.g., artifact; biographical; cultural phase or period; deity; document; equipment; general term; legal term; material; monument class or category; site, monument, or area of archaeological importance; and technique.
The dictionary -- Quick reference -- 1. Principal international conventions and recommendations concerning the preservation of archaeological and historic sites and artefacts -- 2. Principal stratigraphic subdivisions of the Cenozoic era -- 3. Principal stratigraphic subdivisions of the Quaternary System in northwest Europe -- 4. Principal geostratigraphic and biostratigraphic subdivisions of the late Devensian and Flandrian stages in the British Isles -- 5. Correlation of the principal geostratigraphic stages of the Pleistocene series in Europe and North America -- 6. Principal periods, industrial stages, and traditions of the British Bronze Age -- 7. Principal cultural phases in the Americas -- 8. Egyptian rulers and dynasties -- 9. Roman emperors -- 10. Leaders, rulers, kings, and queens of England to ad 1066 -- 11. Selected archaeological websites and portals.
Includes bibliographical references.
Keywords: Archaeology -- Dictionaries; Antiquities -- Dictionaries; Reference works